Parents' Impact on Children's School Performance: Marital Satisfaction, Parental Involvement, and Mental Health. - Lui, Ming; Lau, Gilbert K.; Tam, Vicky C.; Chiu, Hiu-Man; Li, Sandy S.; Sin, Kuen-Fung (Journal of Child & Family Studies, 2020)
Objectives: The present study aims to formulate a conceptual model of the mediating factors between parents' marital satisfaction and children's academic performance, with a sample drawn from Hong Kong Chinese parents and children. The mediators included parental involvement, parents' psychopathological symptoms, and children's internalizing behavior and school engagement. Methods: Survey responses from 507 Grade 4–6 children and their parents, who were primary caregivers, were analyzed. Confirmatory factor analysis was used to examine the internal structures of the seven scales, and the finalized scales have moderate to high reliabilities (Cronbach's α values ranging from 0.74 to 0.95). Structural equation modeling analysis was applied to test the relationships between the latent variables in the proposed model. Results: Structural equation modeling revealed that parents' marital satisfaction had a significant indirect effect on children's academic performance via two pathways: (1) with parents' psychopathological symptoms, children's internalizing behaviors, and school engagement as mediators; (2) with parental involvement and school engagement as mediators. Marital satisfaction had no direct effect on school engagement or on academic performance. Conclusions: Our findings highlighted the importance of parents maintaining harmonious relationships with their spouses and being highly involved in their children's education, in order to provide an optimal social environment to promote children's academic development.